AKTUALISASI KONSEP SABAR DALAM PERSPEKTIF AL-QUR’AN (Studi Terhadap Kisah Nabi Ayub) - Sholiha, Zukhrifa ?Amilatun; muaziroh, ulfa (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2018)
Patient is a half of iman, a secret happiness of human being, a source for strenght on trials, provision of a muslim when disaster happen, and fitnah which always continued and a weapon of sufi againts his lust, to provide him consistent doing syariat allah,and keep him from a bad ravine. Patience itself turns into three kinds. First, be patient in obedience to God. Second, patience from disobedience. Third, patience and trials. All of that (obedience, disobedience, and temptation) is a sin of life. By the difference in patience is faith because every branch of the faith is patient nature. The thing that is not isolated from the nature of patience is taslim (surrender) and pleasure to the destiny (qadha) which has been set by Allah. He gives something diferrent than the other to people who patient. People who patient given blessing, grace,and directions. People who have iman can be patient when trials and obstacle happen. So that, he deserve get reward from his god. Behind every disaster. Theres always a great gift that allah has prepared for you.